The cycle of M. Magauins «orainary tales». (Eurasian Journal of Philology Science and Education, 2015)
In this article analyse the projects of Kazack literature classic, heroes writer which, is written in the ends of M.Magauin life. And article analyse of sides such us theme style. The article analyse with the history send andconsider the way development Kazack prose, social victims that inftunce to the processe of Kazack literature, so that the article analyse the average and style of Kazack stories. When analyse the stories which calls «orainary tales» that enter to the sclim project, it helps to discuse about village problems. Its about of proijets which wrote M.Magauin. In this stories there are many subjects which about village prose. And it says that village prose is very difficult. In this article words of writen is very beautiful and effection.
Keywords: artistic tales; viliage prose; literature process; artistic form; the world of literature